Study of the Influence of Rolling Modes and Regimes on the Physical and Mechanical Properties of the Thread (Eurasian Journal of Research, Development and Innovation, 2022)
The article presents studies of the regularity of the influence of the diameter of the workpiece for thread rolling on the resulting thread profile by rolling with two rollers on the stop.